Conditions and Sustainability Status of Mangrove Island Karimun Big - Jaki Mochtar; Bambang Widigdo; Fery Kurniawan (Budapest International Research and Critics University, 2022)
The types of mangrove vegetation found on Karimun Besar Island consisted of A. lanalata, R. mangle, Xylocarpus sp., Nypa fruticans, Bruguiera sp., Lumnitzera racemosa. This species is spread unevenly on Karimun Besar Island. The highest INP was Xylocarpus species at station 3, West Meral District, which was 191.42%. The highest INP at station 1 type A. lanalata was 155.80%. The highest INP at station 2 type R. mangle was 155.44%. The highest INP at station 4 types of R. mangle is 150.93%. The highest INP at station 5 species A. lanalata was 162.91%. The highest INP at station 6 species of Xylocarpus was 198.82%. The highest INP at station 7 Bruguiera species is 137.51%. The highest INP at station 8 types of Lumnitzera racemosa is 175.35%. To manage the mangrove ecosystem on Karimun Besar Island, an integrated and sustainable management is needed. For this reason, an analysis of the sustainability status was carried out with 20 attributes and 4 dimensions, namely: the ecological dimension, the economic dimension, the social dimension and the legal and institutional dimension. The results of the analysis show that the multidimensional sustainability index is 41.44. Mangrove ecosystem management in a sustainable and integrated manner by prioritizing the management of the use of coastal areas, the availability of landfill waste, management of groundwater utilization, utilization of processed products from mangroves and mangrove rehabilitation.